Structural model of health anxiety based on intolerance of uncertainty and anxiety sensitivity with mediating the role of rumination in college students - Partovi pirooz, Leila; Jomehori, Farhad; Seadatee Shamir, Aboutaleb; Hasani, Jafar (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and Aim: The purpose of this research was to investigate the structural model of health anxiety based on uncertainty intolerance and anxiety sensitivity with the mediation of rumination in students. Research method: This descriptive research project was conducted with structural equation modeling and with the presence of 454 people with the online sampling method among the students of Azad University, Science and Research Unit in the academic year of 1401-1400. To measure the research variables, Salkoskis et al.'s Short List of Health Anxiety (2002), Friston et al.'s Intolerance Scale (1994), Reiss et al.'s Anxiety Sensitivity Questionnaire (1986) and Nolen-Hoeksma and Maro's (1991) rumination response scale were used. Became. Data were analyzed with Pearson correlation coefficient and structural equations using SPSS and AMOS software version 24. Results: The results showed that there is a significant relationship between uncertainty intolerance, anxiety sensitivity and rumination with health anxiety (P